2020
DOI: 10.1302/2046-3758.94.bjr-2019-0274.r1
|View full text |Cite
|
Sign up to set email alerts
|

Induction heating for eradicating Staphylococcus epidermidis from biofilm

Abstract: Aims Induction heating is a noninvasive, nonantibiotic treatment modality that can potentially be used to cause thermal damage to the bacterial biofilm on the metal implant surface. The purpose of this study was to determine the effectiveness of induction heating on killing Staphylococcus epidermidis from biofilm and to determine the possible synergistic effect of induction heating and antibiotics. Methods S. epidermidis biofilms were grown on titanium alloy (Ti6Al4V) coupons for 24 hours (young biofilm) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
3
18
2
Order By: Relevance
“…A previous study by our group demonstrated that P. aeruginosa biofilm was more susceptible to ciprofloxacin after AMF treatment 22 . Pijls et al 24 , 35 reported similar results as was seen in this study, that there was an enhanced effect with AMF and antibiotics in Staphylococcus epidermidis and S. aureus biofilms on titanium alloy than with either treatment alone. One concern for the clinical adoption of AMF relates to therapeutic index, specifically the ability to reduce biofilm through thermal effects while minimizing neighboring tissue damage.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study by our group demonstrated that P. aeruginosa biofilm was more susceptible to ciprofloxacin after AMF treatment 22 . Pijls et al 24 , 35 reported similar results as was seen in this study, that there was an enhanced effect with AMF and antibiotics in Staphylococcus epidermidis and S. aureus biofilms on titanium alloy than with either treatment alone. One concern for the clinical adoption of AMF relates to therapeutic index, specifically the ability to reduce biofilm through thermal effects while minimizing neighboring tissue damage.…”
Section: Discussionsupporting
confidence: 88%
“…This model has been described elsewhere. 17 , 18 The biofilm was grown by immersing the coupons in 300 ml of growth medium (brain heart infusion (BHI)), inoculated with S. aureus (single colony from agar plate) and incubated for seven days at 37°C. The growth medium was not changed during these seven days.…”
Section: Methodsmentioning
confidence: 99%
“…This temperature and duration were chosen as they were expected to be effective and practical while minimizing the risk of necrosis. 13 , 17 , 21 The thermal shock was delivered in a non-contact manner using a custom-built induction heater with non-contact infrared temperature control. This system has been validated and described previously ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In addition to biofilm formation on implants, these bacteria can spread into bone matrix and the bone cells, causing inflammation and thereby interfering with the normal bone healing process. [5][6][7] Currently, new methods are being tested for treatment of biofilm-associated bone infection, namely the use of bone cement loaded with circulating drugs, 8 use of shockwaves, 9 and heat induction in combination with antibiotics. 10 Previously, S. aureus was considered an extracellular pathogen.…”
Section: Introductionmentioning
confidence: 99%